The effect of bullying intervention program based on internet gaming disorder and emotion regulation skills on bullying behaviors of primary school students - Öztürk, İsmail; Traş , Zeliha (Journal of Dependence, 2024)
Objective: The aim of this study was to investigate the effect of an intervention program based on internet gaming disorder and emotion regulation skills on elementary school students' bullying behaviors.Method: A semi-experimental design with pre-test, post-test, and follow-up measurements was used. The study group consisted of a total of 36 individuals, with 18 in the experimental group and 18 in the control group. The Peer Bullying Scale, Internet Gaming Disorder Scale, and Cognitive Emotion Regulation Scale were used as data collection tools.Results: When examining the pre-test, post-test, and follow-up test results of the experimental and control groups, it is observed that bullying score averages and internet gaming disorder score averages show a significant decrease in the experimental group.Conclusion: The intervention program based on internet gaming disorder and emotion regulation skills proves to be effective in reducing bullying behaviors among elementary school students.
Keywords: Bullying; internet gaming disorder; emotion regulation skills; bullying intervention program